Experimental Analysis of Microstructured Steel Surfaces for Wet Tribological Applications in the Low Velocity Regime. (5th May 2015) - Chlipala, Mateusz; Schneider, Johannes; Schulze, Volker
Abstract : The surface topography plays an important role in the design of a function-optimised surface. Therefore, the influence of topography with microsized structures produced by laser surface texturing (LST) is experimentally examined under lubricated sliding conditions. The structured specimens were made of AISI 51200 (DIN 100Cr6) hardened to about 800 HV. Concerning the requirements of tribological testing without any debris caused by the preprocessing, the structuring was carried out using a picosecond laser system (Trumpf TruMicro) with 6 ps pulse duration. A laboratory pin-on-disc tribometer (Plint TE-92 HS) was used for the tests, which were run under wet conditions with counterbodies made of bronze and steel at a nominal contact pressure of up to 4 MPa and sliding speeds between 0.04 and 2.0 m/s. Furthermore, start-stop cycles with accelerating and decelerating shares were used to simulate an automotive start-stop system. In the tribological experiments, a significant reduction of the friction coefficient was observed compared to sliding pairs without microstructured pin surfaces. Whereas no measureable wear occurred on the steel pins and discs, the bronze discs showed a significant amount of wear and the microstructures on the pin surfaces mated against bronze discs were almost completely filled with wear debris.